2018
DOI: 10.1002/anie.201806146
|View full text |Cite
|
Sign up to set email alerts
|

A Nonheme Sulfur‐Ligated {FeNO}6 Complex and Comparison with Redox‐Interconvertible {FeNO}7 and {FeNO}8 Analogues

Abstract: A nonheme {FeNO} complex, [Fe(NO)(N3PyS)] , was synthesized by reversible, one-electron oxidation of an {FeNO} analogue. This complex completes the first known series of sulfur-ligated {FeNO} complexes. All three {FeNO} complexes are readily interconverted by one-electron oxidation/reduction. A comparison of spectroscopic data (UV/Vis, NMR, IR, Mössbauer, X-ray absorption) provides a complete picture of the electronic and structural changes that occur upon {FeNO} -{FeNO} interconversion. Dissociation of NO fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…We speculated that a mononuclear nonheme iron center, with an appropriate ligand environment, might have the minimal attributes needed to activate NO toward N−N bond formation and N−O cleavage to give N 2 O, circumventing the need for a dinuclear system by taking advantage of the diffusional reactivity accessible to small molecules. Our initial efforts led to a sulfur‐ligated mononuclear iron complex ([Fe II (N3PyS)] + ) that supported the binding of NO in a rare series of redox‐interconvertible {FeNO} 6–8 species with identical ligand environments [12] . Reversible one‐electron reduction of the {FeNO} 7 complex gave an {FeNO} 8 complex, which then decayed to produce N 2 O in sub‐stoichiometric yield (54 %) [13] .…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that a mononuclear nonheme iron center, with an appropriate ligand environment, might have the minimal attributes needed to activate NO toward N−N bond formation and N−O cleavage to give N 2 O, circumventing the need for a dinuclear system by taking advantage of the diffusional reactivity accessible to small molecules. Our initial efforts led to a sulfur‐ligated mononuclear iron complex ([Fe II (N3PyS)] + ) that supported the binding of NO in a rare series of redox‐interconvertible {FeNO} 6–8 species with identical ligand environments [12] . Reversible one‐electron reduction of the {FeNO} 7 complex gave an {FeNO} 8 complex, which then decayed to produce N 2 O in sub‐stoichiometric yield (54 %) [13] .…”
Section: Introductionmentioning
confidence: 99%
“…22 Pioneered by Wieghardt et al reporting the first comprehensive characterization of the lowspin {FeNO} [6][7][8] complexes, 23 a series of {FeNO} [6][7][8] and highly reduced {FeNO} [8][9][10] complexes have been spectroscopically and structurally characterized. [24][25][26][27] Lehnert group reported the first series of high-spin {FeNO} [6][7][8] complexes and demonstrated that the redox transformation of high-spin {FeNO} [6][7][8] were all ironbased contrasted to corresponding low-spin complexes where redox transformation was generally NO centered. 28 Most recently, Meyer and coworkers synthesized an complete series of five {FeNO} [6][7][8][9][10] complexes with one ligand scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Lancasters Gruppe untersucht Beziehungen zwischen elektronischer Struktur und Funktion bei Katalysen mit unedlen Metallen in Synthese und Biologie mit Schwerpunkten auf C‐H‐Funktionalisierung und Ammoniakoxidation. In einer Zuschrift in der Angewandten Chemie verglich er verschiedene Eisen‐Nitroso‐Komplexe mit Schwefelliganden …”
Section: Ausgezeichnet …unclassified